The role of modern information resources in the teaching of foreign students of medical university - Ancheva, I. A. (Journal of Education, Health and Sport, 2017)
Ancheva I. A. The role of modern information resources in the teaching of foreign students of medical university. Journal of Education, Health and Sport. 2017;7(1):284-292. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.260173 http://ojs.ukw.edu.pl/index.php/johs/article/view/4197 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK 61: 378.147 : 004]-054.6 THE ROLE OF MODERN INFORMATION RESOURCES IN THE TEACHING OF FOREIGN STUDENTS OF MEDICAL UNIVERSITY I. A. Ancheva Odessa National Medical University, Ukraine, Odessa irina.an-va@rambler.ru Summary Ensuring a high level of clinical training of medical students in higher institutions and improving the quality of teaching remain the most important aims. The purpose of study was examination of the most frequently used sources of information in obstetrics and gynecology, resorted to by English-speaking students during self-study based on a large volume of available information. The materials were the results of the foreign students` survey. The article has described and analyzed modern and optimal forms of teaching the discipline of obstetrics and gynecology to foreign students of the medical university, taking into account the possible use of different information resources. Keywords: information resources and technologies, mobile applications, the system of higher medical education, English-speaking students.